Objetos Virtuales de Aprendizaje Para el Estudio de Ecuaciones Lineales y Cuadráticas - Tixe Zumba, Wilmer Ernesto (2024)
The use of technology in all subject areas is required by current educational trends, hence the field of mathematics has worked to enhance the caliber of instruction and learning by utilizing digital resources like Virtual Learning Objects (VLOs). The objective of this study was to describe how first-year baccalaureate students at Milenio Educational Unit, Penipe, study linear and quadratic equations using virtual learning objects (VLOs). This research took a quantitative approach with a quasi-experimental design because it worked with two distinct groups of application, field, and transversal types, as well as an explanatory level. On the other hand, data were collected from a purposive non-probability sample of 42 students classified into 2 groups, the first one named control group of 20 students and the other as experimental group of 22 students; a test technique and a questionnaire instrument were applied. The results revealed that the use of Virtual Learning Objects (VLOs) such as Prezzi, Genially, Cokitos, Canva, videos, Socrates, and others, had a favorable impact on the study of this subject, so the application of these (VLOs) are recommended in mathematics teaching and learning. Similarly, it attracted the attention of learners in a more creative, original, and participatory manner.